2008
DOI: 10.1001/archpsyc.65.10.1185
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity and Early Predictors of Peer-Victimization Trajectories in Preschool

Abstract: Early childhood preventive interventions should target parenting skills and child behaviors, particularly within families with insufficient income. Together, these risks confer a heightened likelihood for continued peer victimization as rated by mothers, teachers, and the children themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
153
3
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(182 citation statements)
references
References 185 publications
19
153
3
7
Order By: Relevance
“…These analyses were framed to examine whether young aggressors are less selective in their choice of targets. It is vital to understand more about these social processes involving the wider peer‐group in early childhood, which may be particularly beneficial for prevention and intervention programs among this age group (Barker et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…These analyses were framed to examine whether young aggressors are less selective in their choice of targets. It is vital to understand more about these social processes involving the wider peer‐group in early childhood, which may be particularly beneficial for prevention and intervention programs among this age group (Barker et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Teachers were asked to indicate how frequently each type of behavior had occurred for the child during the past three months. Equivalent teacher ratings of peer victimization at school entry have been related to child self-ratings as well as to mother ratings of peer victimization in a normative population-based sample of English-speaking and French speaking children (Barker et al 2008). For each item, the response scale ranged from 0(never), 1(sometimes), to 2 (often).…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…This developmental period was selected because individual differences in theory of mind in preschool children have been found to predict individual differences in social behavior at the beginning of schooling (Cutting and Dunn 2002;Dunn 1995;Runions and Keating 2007; Renouf et al 2010). Moreover, evidence suggests that a substantial amount of kindergarteners are already exposed to peer victimization (Barker et al 2008;Kochenderfer and Ladd 1996). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Where they have been investigated, findings regarding the impact of socio-economic conditions (Wolke et al 2001, Due et al 2009, parenting and bullying are inconsistent (Georgiou 2008, Veenstra 2005. Some studies have found that social deprivation, low father involvement, low parent support or low levels of family cohesion (Hart et al 2000) or harsh and reactive parenting (Barker et al 2008) and maltreatment (Shields and Cicchetti 2001) predicted victimisation. In contrast, others reported that socio-economic status is not related to victimisation (Wolke et al 2001) and that victims more often come from families characterised by high levels of cohesion (Bowers et al 1992), high levels of parental involvement and support (Bowers et al 1992, Baldry and Farrington 1998, Haynie et al 2001, Bowers et al 1994 and parental overprotectiveness (Berdondini and Smith 1996, Georgiou 2008, Perren and Hournung 2005.…”
Section: Introductionmentioning
confidence: 99%